Pengaruh Pajak, Kepemilikan Asing, Intangible Asset Terhadap Transfer Pricing Dimoderasi Ukuran Perusahaan Pada Farmasi Manufaktur BEI 2020-2024 - Aryfianti, Desi; Pardede, Tiolina Evi (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to comprehensively examine the effect of the effective tax rate, foreign ownership, and intangible assets on transfer pricing practices, with firm size serving as a moderating variable, in pharmaceutical manufacturing companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The research adopts a quantitative approach and applies a purposive sampling technique, resulting in a final sample of 10 companies that meet the predetermined criteria. Panel data regression analysis with moderation effect testing is employed to evaluate both direct and interaction effects among the variables. The empirical findings reveal that the effective tax rate and intangible assets do not exert a statistically significant influence on transfer pricing practices. In contrast, foreign ownership demonstrates a significant negative effect, indicating that higher levels of foreign shareholding tend to reduce the intensity of transfer pricing activities. Moreover, firm size does not moderate the relationship between the effective tax rate and intangible assets with transfer pricing, but it significantly strengthens the association between foreign ownership and transfer pricing. These results imply that within Indonesia’s highly regulated pharmaceutical industry, transfer pricing decisions are more strongly driven by ownership structure, corporate governance mechanisms, and the complexity of intra-group transactions rather than by tax minimization incentives alone. Overall, this study is expected to contribute to the enrichment of transfer pricing literature, provide empirical evidence in emerging market contexts, and offer valuable insights for policymakers and tax authorities in designing more effective regulatory frameworks and supervision strategies.